Impact on student learning: National Board Certified Teachers' perspectives - Teresa M. Petty; Amy J. Good; Laura K. Handler (Arizona State University, 2016)
The purpose of this study is to report National Board Certified Teachers' (NBCTs) perceived impact on student learning. The guiding research question for this study, "How do teachers perceive the influence of the National Board Certification process on student learning in their own classrooms?" was explored. A total of 496 NBCTs currently teaching in North Carolina public schools completed the survey questionnaire in which they responded to demographic questions, Likert item questions, and open-ended questions. More than 80% of the study's participants reported the certification process had positively influenced student learning in their classrooms. Thematic analysis revealed several reoccurring themes that NBCTs reported having impact on student learning in their classrooms. These included impact on academic achievement, improved teaching, and/or an increase of effective evaluation and assessment strategies.